Laparoscopic vs. Open Pyloromyotomy in Treatment of Infantile Hypertrophic Pyloric Stenosis - Ibrahim Ismail; Radi Elsherbini; Adham Elsaied; Kamal Aly; Hesham Sheir (Frontiers Media S.A., 2020)
Background/Purpose: Laparoscopic pyloromyotomy gained wide popularity in management of pyloric stenosis with contradictory results regarding its benefits over classic open approach. This study aimed at comparing both regarding their safety, efficiency, and outcome.Methods: This is a prospective randomized controlled study performed from April 2017 to April 2019. It included 80 patients, divided randomly into two groups, where laparoscopic pyloromyotomy was performed in group A and open pyloromyotomy in group B. Both groups were compared regarding operative time, post-operative pain score, time required to reach full feeding, hospital stay, complications, and parents' satisfaction.Results: Median operative time was 21 min in group A vs. 30 min in group B (P = 0). Pain Assessment in Neonates scores were generally higher in group B with more doses of analgesics required (P = 0). Mean time needed to reach full feeding was 15.2 and 18.8 h in groups A and B, respectively (P = 0). Median hospital stay was 19 h in group A and 22 h in group B (P = 0.004). Parents' satisfaction also was in favor of group A (P = 0.045). Although no significant difference was reported between both groups regarding early and late complications, some complications such as mucosal perforation and incomplete pyloromyotomy occurred in the laparoscopic group only.Conclusion: Laparoscopic pyloromyotomy was found superior to open approach regarding faster operative time, less need of analgesics, easier development of oral feeding, shorter hospital stay, and better parents' satisfaction. Yet, there are still some concerns about the safety and efficiency of this procedure over open technique.